(untitled) (Journal of Medical & Health Sciences Review, 2026)
Background: Rectal foreign bodies are a rare but serious surgical emergency that can lead to serious problems if they aren’t diagnosed or treated right away. Early evaluation and the right action are necessary to avoid illness. Case Presentation: We present a patient who arrived at the emergency department with rectal discomfort after the insertion of a foreign body per rectum. The patient was stable in terms of blood flow and had no signs of peritonitis. A plain abdominal X-ray showed a foreign body that was not visible on the X-ray and was in the rectum, but there was no sign of a bowel perforation. The foreign object was successfully taken out through the anus while the patient was under general anaesthesia, so there was no need for surgery. There were no problems during or after the surgery. Conclusion: This case shows that early diagnosis, the right imaging, and timely trans anal extraction under general anaesthesia can all lead to successful non-operative management of rectal foreign bodies. A structured and multidisciplinary approach is important because it makes sure that the patient is relaxed enough for the surgery to be safe and lowers the risk of iatrogenic injury.